Promotion Media Moderates Price and Brand Image on Baba Parfume Purchase Decision - Matondang, Zulaika; Nasution, Hamni Fadlilah; Dwi Ayunda, Sheilla (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study aims to determine the influence of brand image and price on the purchasing decision of Baba Parfum, utilizing promotion media as a moderating variable. The population for this research was students of the Faculty of Economics and Islamic Business (FEBI) at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, with a sample size of 92 respondents. The research was analyzed using Moderated Regression Analysis (MRA). The results of the study, conducted with a 95 percent confidence level (based on a 5% significance level), indicate that Brand image influences the purchasing decision of Baba Parfum, However, promotion media weakens the influence of brand image on the purchasing decision of Baba Parfum. This occurs because the promotional effect is significantly strong, becoming more dominant compared to the already established brand image. Price influences the purchasing decision of Baba Parfum, Furthermore, promotion media strengthens the influence of price on the purchasing decision of Baba Parfum. This happens because promotion media makes consumers more aware of price information, thereby enhancing their value perception, which leads to price becoming the dominant factor in influencing the purchasing decision.